Rainfall- and Irrigation-Induced Landslide Mechanisms in Loess Slopes: An Experimental Investigation in Lanzhou, China - Wei Liu; Ruiqiang Bai; Xinran Sun; Fang Yang; Weiji Zhai; Xing Su (Atmosphere, 2024)
To reveal the mechanism of rainfall- and irrigation-induced landslides in loess slopes within cold regions, a series of tests on loess samples subjected to different permeability durations were conducted, and the effects of rainfall on several performance indicators, including the permeability coefficient, composition, microstructure, soil–water characteristic curve, and the shear strength of the loess, were investigated. The results show that the permeability coefficient of the loess decreased by 68% after permeability testing. With increased permeability duration, there is a marked decrease in total dissolved solids, sand particles, and clay particles, contrasted with an increase in silt particles. This dynamic alters the original soil structure and impacts the soil–water characteristic curve of the loess. Additionally, rainwater infiltration heightens the effective saturation of the loess, in turn diminishing the shear strength of the loess as effective saturation increases. This reduction in shear strength is further intensified with extended infiltration time (or rainfall duration). A landslide is triggered once the shear strength diminishes to the level of the geostatic stress of the loess slope, and the influence of the rainfall-induced loss of soil shear strength should be taken into account during slope stability analysis. This study enhances the understanding of the initiation mechanisms of rainfall-induced landslides in loess slopes.